Integrating Enterprise Risk Management And Business Strategy To Enhance Firm Performance: The Mediating Role Of Competitive Advantage In Indonesia’s Manufacturing Sector - Gabriela Arum Handayani; Maria Ulpah (UNIVED Press, 2025)
This study investigates the impact of Enterprise Risk Management (ERM) and business strategy—specifically cost leadership—on firm performance, with a particular focus on the mediating role of competitive advantage. The research sample comprises 60 manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. ERM disclosures were measured using content analysis of annual reports, while financial and strategic data were collected from firm financial statements published on the IDX website and the Refinitiv Eikon. A panel regression method was employed to analyze the data using STATA software, testing both direct and indirect relationships among the variables. The empirical results indicate that ERM does not have a significant effect on firm performance, whether measured by Return on Assets (ROA) or Tobin’s Q, either directly or through competitive advantage. In contrast, the cost leadership strategy shows a significant positive influence on financial performance. Furthermore, competitive advantage is found to partially mediate the relationship between cost leadership and firm performance.